CONFORTO TÉRMICO EM BIBLIOTECA UNIVERSITÁRIA: ESTUDO DE CASO NO CAMPUS SANTA BÁRBARA D'OESTE DA UNIVERSIDADE METODISTA DE PIRACICABA - Novoletti, Amanda Louvandini; Castro, Adriana Petito de Almeida Silva; Rancura, Raquel L; D'oeste, Carla Matheus (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Adequate microclimatic conditions are important in any built environment, especially in school environments, classrooms, libraries, study rooms, living spaces, cafeterias, among others. Considering that the physical facilities of a library should provide people with a comfortable environment for the development of their activities, as well as offer favorable conditions for the preservation of the collection, this work focused on analyzing the thermal comfort conditions of Library X through measurements of environmental variables in loco, in summer and winter conditions. The focus is to analyze the current situation of the thermal comfort of the studied environment, exposing data of temperature and relative humidity, following the criteria established in legislation. The measurements were performed for three consecutive days, at 9:00 a.m., 12:00 a.m., 3:00 p.m. and 4:00 p.m., using the Digital Globe Thermometer (TGD-200). From the results, it is concluded that the Library does not present conditions of thermal comfort, with some reservations. The results indicate values of relative humidity within the parameters of human comfort, but outside the recommended parameter for the collection. Regarding temperature, this was above the recommended value for both human comfort and the collection.